A Secure and Efficient Handover Authentication Protocol for Wireless Networks - Weijia Wang; Lei Hu (Sensors, 2014)
Handover authentication protocol is a promising access control technology in the fields of WLANs and mobile wireless sensor networks. In this paper, we firstly review an effcient handover authentication protocol, named PairHand, and its existing security attacks and improvements. Then, we present an improved key recovery attack by using the linearly combining method and reanalyze its feasibility on the improved PairHand protocol. Finally, we present a new handover authentication protocol, which not only achieves the same desirable effciency features of PairHand, but enjoys the provable security in the random oracle model.